Genetic analysis of yield components and fiber quality parameters in upland cotton - Tanwir Ahmad Malik, Bilal Nawaz, Saira Sattar, (International Multidisciplinary Research Journal, 2019)
The experiment was laid to analyze genetic features, genotypic and phenotypic correlation coefficients, path analysis with regression analysis among yield contributing traits in a selected F3 populations of upland cotton including parents. In this research experiment ANOVA showed significant difference among all individual plants in F3 populations. Monopodia per plant and bolls per plant possessed maximum value of PCV% and GCV%. Maximum broad sense heritability (≥ 90) was found in all recorded traits except seeds per boll, fiber length and lint percentage. Correlation studies revealed that Seed cotton yield positively correlated with all yield contributing traits i.e. plant height, monopodial branches per plant, Number of bolls per plant, boll weight, lint weight, seed index, lint index, seeds per boll, fiber fineness, fiber strength and fiber uniformity at both genotypic and phenotypic level whereas it depicted negative relationship with staple length. Path coefficient analysis showed that maximum direct positive effect was found of lint weight (2.6005) on seed cotton yield followed fiber fineness (1.2628), seed index (1.1449) and bolls per plant (1.0027). Regression study exhibited that maximum value of R2 for lint weight (0.9509) and boll weight (0.3735) depicted that 95.09% and 37.35% variation in the seed cotton yield, due to its relationship with lint weight and boll weight. It is concluded that there is a great genetic potential in F3 populations for mostly yield contributing traits for further enhancing yield. So those traits should be used as selection criteria during breeding for yield.